Upaya Meningkatkan Gerak Lokomotor Melalui Permainan Engklek Untuk Kelompok B TK Dahlia Indah - Arief Rahman; Imanuddin Siregar (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
Locomotor movement as one aspect of physical motor development that needs attention, especially in kindergarten. Some experts suggest that locomotor movement is related to learning ability. This article examines the locomotor movement of kindergarten children group B and hopscotch games. The increase in locomotor movement through hopscotch games in group B of Dahlia Indah Kindergarten in this study was shown by an increase in the percentage in cycle I, namely 33.33% in the good category and because there were improvements from several shortcomings in cycle I in cycle II, it increased to 86.66% in the good category. Based on the research that has been done, it can be concluded that with interesting and fun learning through hopscotch games, children's locomotor movement can be improved